Effect of testosterone undecanoate on hematological profiles, blood lipid and viscosity and plasma testosterone level in castrated rabbits - Zhao, Chen; Moon, Du Geon; Park, Jong Kwan (Canadian Urological Association Journal, 2013)
Objective: The association between testosterone replacement therapy and cardiovascular risk remains controversial. Blood viscosity is a known individual risk factor for cardiovascular disease mortality. The objective of the present study was to investigate the effects of the long-acting injectable testosterone undecanoate (TU) on risk factors of cardiovascular disease. Methods: Twenty four male New Zealand white rabbits (2.5 kg) were randomly divided into three groups of eight. The first group was used as control. The second group was castrated bilaterally. The third group was administrated with 6 mg/kg of TU at 1 day and 6 weeks after castration. Whole blood viscosity, total plasma testosterone, hemoglobin (Hb), hematocrit (Hct), fibrinogen (FBN), total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) levels were measured at baseline, 6 weeks and 18 weeks. Results: In control group, whole blood viscosity and FBN were significantly increased at 6 and 18 weeks. Castration significantly increased the levels of TC, TG, HDL-C and LDL-C, but decreased Hct and Hb. In the TU injection group, whole blood viscosity was markedly decreased in all share rates, whereas the FBN level was increased. Hb and Hct showed a tendency for higher concentration at 6 weeks. Conclusions: Long-acting injectable TU provides another reliable treatment option for testosterone replacement therapy. Moreover, the patients may receive additional beneficial effect in lowered whole blood viscosity.